2023
DOI: 10.2217/cns-2022-0020
|View full text |Cite
|
Sign up to set email alerts
|

H3G34-mutant diffuse hemispheric glioma with osseous metastases: a case report and literature review

Abstract: Aim: H3G34 diffuse hemispheric glioma is a CNS tumor that is difficult to diagnose and treat and accompanied with poor prognosis. It is becoming clear that extra CNS metastasis may present in a subset of patients with H3G34 gliomas, further complicating diagnosis and treatment. Materials & methods: We present a case of a 19-year-old female with a H3G34 mutant diffuse hemispheric glioma with osseous metastases. We then provide a literature review of the most recent understanding of H3G34 mutant malignancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Reasons for initial presentation were most frequently signs and symptoms of high intracranial pressure (headache, nausea, vomiting, blurred vision, or somnolence), focal neurologic deficits, and seizures. Metastasis was uncommon but did occur in four cases, with the most common patterns being osseous metastasis and a leptomeningeal spread [69,109,110,114].…”
Section: Baseline Information and Clinical Presentation Of Patients W...mentioning
confidence: 95%
See 2 more Smart Citations
“…Reasons for initial presentation were most frequently signs and symptoms of high intracranial pressure (headache, nausea, vomiting, blurred vision, or somnolence), focal neurologic deficits, and seizures. Metastasis was uncommon but did occur in four cases, with the most common patterns being osseous metastasis and a leptomeningeal spread [69,109,110,114].…”
Section: Baseline Information and Clinical Presentation Of Patients W...mentioning
confidence: 95%
“…A number of studies reported on clinical presentation and/or survival [66][67][68][69][70][71][72][73][74][75][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123]. Survival is discussed below with treatment regimens in a separate section.…”
Section: Baseline Information and Clinical Presentation Of Patients W...mentioning
confidence: 99%
See 1 more Smart Citation